2010
DOI: 10.1042/bj20100128
|View full text |Cite
|
Sign up to set email alerts
|

Glial fibrillary acidic protein is elevated in the lysosomal storage disease classical late-infantile neuronal ceroid lipofuscinosis, but is not a component of the storage material

Abstract: Classical late neuronal ceroid lipofuscinosis (LINCL) is a fatal neurodegenerative disease of children caused by mutations in TPP1, the gene encoding the lysosomal protease tripeptidyl peptidase 1. LINCL is characterized by lysosomal accumulation of storage material of which only a single protein component, subunit c of mitochondrial ATP synthase, has been well established to date. Identification of other protein constituents of the storage material could provide useful insights into the pathophysiology of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…PSAP is a known component of the storage material in CLN1 14 and is highly elevated compared with control samples when quantified by MS (Figure 6B). Although not a component of storage material but instead reflecting glial activation, GFAP is elevated in CLN2 43 and other NCLs, and, consistent with this, quantitative MS analysis indicates that levels in the NCL samples are elevated compared with controls. Taken together, the strong correlation between quantitative MS and functional assay data and the detection of specific changes in brain that are predicted from previous studies provide strong validation of the MS-based approach and provide confidence in the interpretation of previously unrecognized protein expression changes in NCL samples.…”
Section: Validation Of Quantitative Proteomic Analysis Of Brain Extra...supporting
confidence: 64%
“…PSAP is a known component of the storage material in CLN1 14 and is highly elevated compared with control samples when quantified by MS (Figure 6B). Although not a component of storage material but instead reflecting glial activation, GFAP is elevated in CLN2 43 and other NCLs, and, consistent with this, quantitative MS analysis indicates that levels in the NCL samples are elevated compared with controls. Taken together, the strong correlation between quantitative MS and functional assay data and the detection of specific changes in brain that are predicted from previous studies provide strong validation of the MS-based approach and provide confidence in the interpretation of previously unrecognized protein expression changes in NCL samples.…”
Section: Validation Of Quantitative Proteomic Analysis Of Brain Extra...supporting
confidence: 64%
“…Altered expression levels of Glial fibrillary acidic protein (GFAP) were found in the MPS IIIB mouse brain. This finding is consistent with previous studies that highlighted a deregulation of GFAP in several lysosomal storage diseases, including MPS IIIB [18,[87][88][89][90][91][92][93][94][95]. The protein GFAP is a molecular marker of astrocytes that are fundamental for the neuronal microenvironment in order to control the metabolism of glucose, neurotransmitters re-uptake, and the formation and maturation of the synapses.…”
Section: Other Proteinssupporting
confidence: 92%
“…Furthermore, a biochemical study analyzing storage isolated from Cln2 Ϫ/Ϫ mice identified material associated with both a lysosomal subcellular fraction and an insoluble protein fraction (Xu et al, 2010). Notably, p62 was found to be the predominant component associated with the insoluble fractions.…”
Section: Discussionmentioning
confidence: 99%